Pelatihan dan Pendampingan Kader Lingkungan Hidup Untuk Generasi Muda Pimpinan Wilayah Muhammadiyah (PWM) Papua - Puguh Sujarta; Suwito Suwito; Irma Rahayu; Suharno Suharno; Farmawaty Farmawaty; Natalie J. Tangkepayung (LPPM Uncen, 2025)
The younger generation has an important role in preserving the environment. The objectives of the community service activities: (1) to introduce environmental cadre training and mentoring programs for the younger generation of PWM Papua; (2) through community service, it can produce outputs in the form of accredited national community service journals. This community service activity was carried out on Monday, August 25, 2025 at the Environmental Assembly - IPM PWM Papua. The methods used were lectures, discussions, and real actions. The activity participants were 21 participants, starting with a pre-test (in the form of a questionnaire) to identify participant knowledge. Then the provision of material about environmental cadres and ending with a post-test with the quizziz.com application. The conclusion is that: (1) Participants were very enthusiastic in participating in community service activities and understanding the environmental cadre training material; (2) Based on the evaluation results, it shows that the level of participant understanding is quite good when seen from the percentage of participant statements and answers.